HUBUNGAN BERAT BADAN IBU SELAMA HAMIL SESUAI IMT DENGAN KEJADIAN BERAT BADAN LAHIR RENDAH (BBLR) DI PUSKESMAS BENTOK KAMPUNG - Hiktiasari, Erlinda; Suhrawardi, Suhrawardi; Rafidah, Rafidah (Seroja Husada: Jurnal Kesehatan Masyarakat, 2025)
Introduction: According to the Maternal Perinatal Death Notification (MPDN) data, 20,882 infant deaths occurred in 2022, primarily due to low birth weight (LBW, 28.2%) and asphyxia (25.3%). In 2023, the Tanah Laut District Health Office reported 402 LBW births, and one neonatal death due to LBW occurred at Bentok Kampung Community Health Center. Mothers with low BMI faced increased risks of delivering LBW babies. Objective: This study aimed to investigate the relationship between maternal BMI during pregnancy and LBW incidence at Bentok Kampung Community Health Center. Methods: This retrospective analytical study employed a case-control design. The population consisted of 323 mothers who gave birth in 2023. Samples included 29 LBW cases and 58 normal birth weight controls, selected through simple random sampling. This research has received ethical approval from Poltekkes Kemenkes Banjarmasin No. 1047/KEPK-PKB/2024. Results: The results showed a significant correlation between maternal BMI during pregnancy and LBW incidence (p-value = 0.000 < 0.05)..Conclusion: Intensive education on maintaining healthy BMI during pregnancy is crucial. Enhancing pregnant women's understanding of balanced nutrition and regular weight monitoring can prevent LBW.